Corporate Sustainability Reporting and Financial Performance of Deposit Money Banks in Nigeria - Korolo, Emmanuel Omolaye; Korolo , Akuboere Salome (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study investigates the relationship between corporate sustainability reporting and the financial performance of deposit money banks in Nigeria. The specific objectives of the study were to determine whether economic, social, and environmental sustainability reporting affects financial performance in Nigeria using return on assets (ROA) as a measure of corporate financial performance. The study's data were sourced from annual reports of sampled banks from 2013-2022. Using the panel least squares regression technique, the study found that economic and environmental sustainability reporting has a negative and positive insignificant effect on the performance respectively. However, social sustainability reporting was found to be negative and statistically significant. Based on the findings, the study recommends amongst others that enabling legislation should be put in place to mandate enhanced sustainability practices among all deposit money banks in Nigeria as well as facilitate meaningful evaluation and measurement of economic, social, and environmental impacts in all areas of bank operations in Nigeria.